Caesium Acetate‐Based Electrolytes for Aqueous Electrical Double Layer Capacitors. Issue 22 (27th October 2022) - Liu, Siqi; Stettner, Timo; Klukas, Ronald; Porada, Thomas; Furda, Kristina; Fernández, Alba Martín; Balducci, Andrea
Abstract: In this work, we report about the use of caesium acetate (CsOAc)‐based electrolytes for Electrical Double Layer Capacitors (EDLCs). We showed that solutions of 6.4 m CsOAc in H2 O, which is a highly concentrated aqueous electrolyte, and 21 m CsOAc in H2 O, which is a Water in Salt Electrolyte (WiSE), display very favourable chemical‐physical properties. EDLCs containing 21 m CsOAc in H2 O as electrolyte display operating voltage of 1.7 V. These devices display good energy density and are able to retain all their initial capacitance after 400 hours of floating at 1.7 V. On the other hand, EDLCs containing 6.4 m CsOAc in H2 O as electrolyte display operative voltage of 1.6 V and are delivering at 10 A g −1 very high energy and power density (4 Wh kg −1 and 14.1 kW kg −1, respectively). Furthermore, they can retain 91 % of their initial capacitance after 400 hours of floating at 1.6 V. This performance, which is among the highest so far reported for aqueous‐based EDLCs, indicates that CsOAc can be considered a very promising salt for the realization of advanced EDLCs. Abstract : Caesium acetate‐based electrolytes exhibit high conductivity and low viscosity. When used in EDLCs they allow the realization of aqueous devices operating at 1.7 V displaying high performance and outstanding cycling stability.